TRANSFORMATION OF WAQF ASSET DEVELOPMENT FINANCING IN MALAYSIA THROUGH DIVERSIFIED DIRECT FINANCING METHODS - Che Khadijah Hamid; Sakinatul Raadiyah Abdullah; Farahdina Fazial; Surita Hartini Mat Hassan; Salimah Yahaya (Journal of Islamic, Social, Economics and Development, 2023)
In recent years, the revitalization of waqf institutions has become an agenda within the global Muslim community, including Malaysia. Waqf is seen to strengthen the economy during the current pandemic phase. The diversification of financing methods for waqf asset development has become a rapidly implemented transformation, capturing the attention and focus of trustees in pursuing the best financing approaches. Among the potential financing methods is direct financing. The question is, how is this direct financing method implemented in Malaysia? In line with this, the objective of this study is to identify the types of direct financing methods in waqf land development. Secondly, to analyze the implementation of this direct financing method in waqf asset development in Malaysia. Data were obtained through semi-structured interviews with waqf officials and practitioners and through secondary data such as writings, journals, articles, and websites of the studied organizations. Content analysis was employed for the analysis. Ultimately, direct financing methods in waqf asset development is gaining momentum today, involving cash waqf methods that encompass various transformations. The transformation in implementing this method has aided in fundraising for waqf asset development, particularly about waqf land, thereby ensuring its productive development and safeguarding the sustainability of waqf asset benefits in Malaysia, specifically.